Method for Determining of the Anti-adhesion Ability of Cutting Fluids - Dugin, Andrey; Jersak, Jan; Popov, Alexey (Manufacturing Technology Journal, 2014)
In most cases, the use of cutting fluids increases machining productivity while cutting different types of materials. Anti-adhesion ability is one of the main properties of cutting fluids increasing the tool life. Companies producing cutting fluids need to acquire information on anti-adhesion abilities of the cutting fluids as well as on anti-adhesion abilities of individual substances and effects for future development of their products. Consequently, methodology for evaluating anti-adhesion ability of cutting fluids was designed. The substance of the method consists in the evaluation of differences in the size of the wear area created under otherwise identical cutting conditions while using different cutting fluids at the front surface of the cutting tool where adhesive wear occurs during the cutting process under certain cutting conditions. The methodology was verified using 11 process fluids.
Keywords: Machining; Cutting fluid; Adhesion; Wear